2019
DOI: 10.1177/1179543319867116
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Entomopathogenic Fungi on the Biology ofSpodoptera litura(Lepidoptera: Noctuidae) and its Reduviid Predator,Rhynocoris marginatus(Heteroptera: Reduviidae)

Abstract: Entomopathogenic fungi (EPFs), Isaria fumosorosea and Beauveria bassiana, are efficient biological agents in the management of multiple arthropod pests. In this study, the effects of both EPF species on various life stages of Spodoptera litura (F.) (Lepidoptera: Noctuidae) and its natural enemy Rhynocoris marginatus (Fab.) (Hemiptera: Reduviidae) were determined under laboratory conditions. I. fumosorosea significantly ( P < .05) reduced the growth rate of the third and fourth instar larvae of S. litura. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…This study has shown that, in unpolluted environment several beneficial and economical species of microbial community can be found including entomopathogenic fungi which have shown to have mortality effect to mosquito vector species and less effect to non-targeted organisms. These findings are similar to previous studies which showed toxicity effect to variety of arthropods [17][18][19]. At present, there is a better consideration of the use of microbial-…”
Section: Discussionsupporting
confidence: 91%
“…This study has shown that, in unpolluted environment several beneficial and economical species of microbial community can be found including entomopathogenic fungi which have shown to have mortality effect to mosquito vector species and less effect to non-targeted organisms. These findings are similar to previous studies which showed toxicity effect to variety of arthropods [17][18][19]. At present, there is a better consideration of the use of microbial-…”
Section: Discussionsupporting
confidence: 91%
“…These results were in line with Nguyen et al (2007) who found that B. bassiana also showed a high reduction in adult emergence from pupae of Helicoverpa armigera using the soil inoculation method and the pupal immersion technique. On the other hand, Ullah et al (2019) found that B. bassiana had insignificant effect on the adult emergence rate of S. litura. Also, Asi et al (2013) expressed the highly resistant behavior of pupae toward fungal infection than other developmental stages of S. litura.…”
Section: Discussionmentioning
confidence: 92%
“…Management of the sucking insect pests is mainly by chemical insecticides but their excessive and indiscriminate use has led to insecticide resistance and residue problems apart from health hazards (Pilkington et al 2010 andPappas et al 2013). Various parasitoids, predators, pathogens, and botanicals are being exploited for management of these pests (Ali et al 2017 andUllah et al 2019). Management of insect pests using entomopathogenic fungi (EPF) is regarded as an important alternative method for organic cultivation of vegetables under protected conditions (Manfrino et al 2014 andAli et al 2018).…”
mentioning
confidence: 99%